Effects of abdominal microcurrent in the consumption and proportion of energy substrates during aerobic exercise: a pilot study - Vilarinho, Rui (2022)
Microcurrent therapy can increase lipolytic activity. However, it is unknown if the increased availability of lipids can influence the selection of energy substrates during a single session of aerobic exercise. We aimed to analyze the effect of microcurrent application to the abdominal region in the consumption of lipids and carbohydrates, and respiratory exchange ratio (RER) during a single session of moderate aerobic exercise in young adults. A pilot study was conducted in which participants were allocated to intervention (IG) or placebo (PG) groups. In both groups, 40 min of microcurrent application with two frequencies (25 and 10 Hz) followed by 50 min of moderate intensity aerobic exercise (45–55% of heart rate reserve) on a cycloergometer were performed. The microcurrent application was performed without intensity in the PG. A portable gas analyzer (K4b2 ) was used during exercise in both groups. Thirty-eight participants (20.6 ± 1.8 years; 18 in IG and 20 in PG) were enrolled. There were no significant differences in the consumption of substrates or RER between the groups during exercise (p > 0.05). Microcurrent application seems to be insufficient to influence the consumption of energy substrates and RER during a single session of aerobic exercise in young adults.